Analisis Pengaruh Pembangunan Detached Breakwater terhadap Perlindungan Garis Pantai di Pulau Bengkalis Menggunakan Penginderaan Jauh - Edi Kurniawan; Sigit Sutikno; Muhammad Yusa (Syntax Corporation, 2023)
The coastline is the boundary between land and sea water whose position is always changing dynamically. Changes in coastlines are caused by disturbances to sediment transport along onshore, reduced sediment supply, disturbances of buildings, and low condition of the cliffs therefore they can’t cover the waves (Ministry of Public Works and Housing, 2015). The purpose of this study is to determine the response of the coastline after the construction of detached breakwater structure on the north coast of Bengkalis Island. Sentinel-2 imagery data used in this study and then analyzed using the Digital Shorelines Analysis System (DSAS) tool. The results of the analysis show that there are have variations of the shoreline response to the structures that have been built. In the period 2016 – 2022 the coastline hase changes, both accretion and abrasion. The maximum change in the forward coastline is 189.09 meters long with an accretion rate of 30.5 meters/year. While the maximum change in the backward coastline is 144.56 meters long with an abrasion rate of 23.32 meters/year. Overall, the construction of detached breakwaters has a positive impact on the coastline, thus increasing the land area on the north coast of Bengkalis Island.